Homebuyer's preferences between sell-thenbuild (STB) and build-then-sell (BTS) / Nurein Fatinie Azmi and Suwaibatul Islamiah Abdullah Sani - Azmi, Nurein Fatinie; Abdullah Sani, Suwaibatul Islamiah (2019)
Housing industry in Malaysia had progressed by leaps and bounds since the onset of the First Malaysia Plan from 1966 until 1970. The Sell Then Build (STB) system is one of housing delivery system that has long been used in Malaysia's housing sector. This system has been extremely uuccessful but the issues such as abandoned projects, late delivery and shoddy workmanship has shaded a shame on this system. Realizing the unfairness of the system to the homebuyers, the Malaysian government agreed to provide an alternative housing delivery system that can serve the rights of the buyers, namely Build Then Sell (BTS). However, there is also an argument that there is no guarantee the homebuyers would be willing to absorb the BTS houses been put in the market because of the anticipated higher price. This paper aims to determine the factors influencing homebuyers' preferences between STB and BTS housing delivery systems; and to compare the most important factor influencing homebuyer's preferences between STB and BTS housing delivery system. The data collection method used is by questionnaire in a survey conducted at property exhibition in Ipoh, Perak. Based on the 267 sets of survey questionnaires, the findings also indicated that BTS system was perceived to be favored by the respondents (53.91% agreement) more than STB system (46.09% agreement).